PR STRATEGY IN HANDLING CUSTOMER COMPLAINTS (COMPLAINT HANDLING) IN MAKASSAR CITY REGIONAL DRINKING WATER COMPANIES (PDAM) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study aims to determine the public relations strategy of PDAM Makassar City in handling customer complaints, as well as to determine the supporting and inhibiting factors of PDAM Makassar City Public Relations in handling customer complaints. This study used a qualitative research method with a descriptive approach. Sources of data obtained are primary data and secondary data. Data collection techniques using three ways, namely, observation, interviews and documentation. The results of the study show that the Public Relations strategy in handling customer complaints at PDAM Makassar City is to handle them consistently using SOP guidelines/Customer complaint acceptance schemes, in addition to handling customer complaints technically and with polite and friendly service. The handling of customer complaints by PDAM Makassar Public Relations has proven to be responsive and responsive. Factors that support public relations in handling customer complaints are all aspects involved in the complaint handling process, while the inhibiting factors are customers who complain emotionally, limited training in PDAM Public Relations HR, network and also an IT system that has errors. With good communication,